2020
DOI: 10.1101/2020.12.09.417808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative genomics provides insight into the function of broad-host range sponge symbionts

Abstract: Sponges have evolved complex associations with conserved bacteria symbionts that contribute to the fitness of the host. Sponges of the family, Latrunculiidae, produce a diverse array of cytotoxic pyrroloiminoquinone alkaloids and their microbiomes are dominated by a conserved spirochete and betaproteobacterium. We investigated the microbiome of Tsitsikamma favus, a latrunculid species that produces predominantly tsitsikammamines. A total of 50 Metagenome-Assembled-Genomes (MAGs) were recovered from the four me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 146 publications
0
2
0
Order By: Relevance
“…In non-marine hosts such as termites, Spirochaetes of the genus Treponema (family: Spirochaetaceae) have been implicated in nitrogen fixation (Lilburn et al, 2001), while in the marine environ- lucinid clams (Lim et al, 2019). Further, Spirochaeta were identified as a key member of the holobiont in Tsitsikamma and Cyclacanthia sponges where cophylogenetic patterns were observed (Matcher et al, 2017) and metagenomic analysis of the sponge-associated Spirochaete suggested roles in vitamin B6 and pyrroloiminoquinone production (Waterworth et al, 2020). The Thaumarcheota genus Nitrosopumilus (family: Nitrosopumiliaceae) is characterised by its ability to convert ammonia to nitrite, providing an essential step in nitrogen cycling (Könneke et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In non-marine hosts such as termites, Spirochaetes of the genus Treponema (family: Spirochaetaceae) have been implicated in nitrogen fixation (Lilburn et al, 2001), while in the marine environ- lucinid clams (Lim et al, 2019). Further, Spirochaeta were identified as a key member of the holobiont in Tsitsikamma and Cyclacanthia sponges where cophylogenetic patterns were observed (Matcher et al, 2017) and metagenomic analysis of the sponge-associated Spirochaete suggested roles in vitamin B6 and pyrroloiminoquinone production (Waterworth et al, 2020). The Thaumarcheota genus Nitrosopumilus (family: Nitrosopumiliaceae) is characterised by its ability to convert ammonia to nitrite, providing an essential step in nitrogen cycling (Könneke et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several sponge symbionts displayed a limited carbohydrate metabolism(Bayer et al, 2020;Knobloch et al, 2020). This metabolic specialization of microbes that represent certain lineages inhabiting a similar environmental niche and encoding equivalent genes for carbohydrate utilization indicates the possible presence of functional guilds within the sponge microbiome(Fan et al, 2012) Waterworth et al, 2021),. supporting the notion that synthesis of these essential molecules represents a microbially-mediated function common within the sponge microbiome(Hentschel et al, 2012;Pita et al, 2018).…”
mentioning
confidence: 99%